Innovation, Investment, and Emerging Opportunities in Today’s Textile and Apparel Value Chain - Manchanda, Sumit; Schlorke, Sabine; Schmitt, Maud (International Finance Corporation, Washington, DC, 2021)
Summary of note 96: innovation, investment, and emerging opportunities in today’s textile and apparel value chain textile and apparel manufacturing is a critical creator of formalized jobs, a well-known path to industrialization, and an enabler of value chain relationships that modernize economies and make them more complex. Today, value chains that support the textile and apparel industries are rapidly evolving. They are integrating new technologies, embracing workplace innovations, adopting sustainable efficiencies, and inventing products and processes to meet the changing demands of global consumers and markets. This pattern has largely been repeating itself since the First Industrial Revolution more than 250 years ago. At the most fundamental level of the textile and apparel value chain, countries with an abundance of low wage, minimally skilled workers enter the industry to do the heavy manual labor and, with time and learned experience, build skills that enable them to graduate to the production of complex products that help them integrate into more important value chains and steadily advance their standards of living.